2017
DOI: 10.1038/srep44494
|View full text |Cite
|
Sign up to set email alerts
|

Platonic Micelles: Monodisperse Micelles with Discrete Aggregation Numbers Corresponding to Regular Polyhedra

Abstract: The concept of micelles was first proposed in 1913 by McBain and has rationalized numerous experimental results of the self-aggregation of surfactants. It is generally agreed that the aggregation number (Nagg) for spherical micelles has no exact value and a certain distribution. However, our studies of calix[4]arene surfactants showed that they were monodisperse with a defined Nagg whose values are chosen from 6, 8, 12, 20, and 32. Interestingly, some of these numbers coincide with the face numbers of Platonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…The N agg number can be controlled by the chemical structure of the surfactants or the solution conditions. For example, it has been reported that QACaL5 (Figure ) exhibits N agg =12 at a NaCl concentration ( C NaCl ) of 50–100 m m and N agg =20 at C NaCl ≥200 m m . This N agg change may be caused by a decrease in the volume of the hydrophilic moiety (the green part in Figure a), which is due to reduced electrostatic repulsion at higher C NaCl .…”
Section: Figurementioning
confidence: 94%
See 4 more Smart Citations
“…The N agg number can be controlled by the chemical structure of the surfactants or the solution conditions. For example, it has been reported that QACaL5 (Figure ) exhibits N agg =12 at a NaCl concentration ( C NaCl ) of 50–100 m m and N agg =20 at C NaCl ≥200 m m . This N agg change may be caused by a decrease in the volume of the hydrophilic moiety (the green part in Figure a), which is due to reduced electrostatic repulsion at higher C NaCl .…”
Section: Figurementioning
confidence: 94%
“…We recently found that calix[4]arene‐derived surfactants form spherical micelles with a defined, monodisperse N agg value of 4, 6, 8, 12, or 20, corresponding to the Platonic solids. We thus refer to these as Platonic micelles.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations